Scholastic's Black culture program - Scholastic Book Services (Scholastic Book Service, 1973)
Discusses some of the trends and developments in black and Afro-American art, dance, music, poetry, and religion.
pt.1. Black art. 77 fr.--pt.2. Black dance. 100 fr.--pt.3. Black music I. 91 fr.--pt.4. Black music II. 79 fr.--pt.5. Black poetry I. 101 fr.--pt.6. Black poetry II. 87 fr.--pt.7. Black religion I. 79 fr.--pt.8. Black religion II. 88 fr.
Mounted as slides in 13 carousels.
Tape copy.
With additional phonodisc entitled Black music III.
With teacher's manual.
Keywords: African American arts -- United States